2020
DOI: 10.1002/hep.31159
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Demonstrates Heterogeneous Growth Patterns in a Multicenter Cohort of Patients With Cirrhosis

Abstract: Background and Aims There are limited data on hepatocellular carcinoma (HCC) growth patterns, particularly in Western cohorts, despite implications for surveillance, prognosis, and treatment. Our study’s aim was to quantify tumor doubling time (TDT) and identify correlates associated with indolent and rapid growth. Approach and Results We performed a retrospective multicenter cohort study of patients with cirrhosis diagnosed with HCC from 2008 to 2017 at six US and European health systems with two or more cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
97
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 42 publications
2
97
2
1
Order By: Relevance
“…However, we noted sex disparities in survival persisted after adjusting for BCLC stage, suggesting this difference is not entirely explained by healthcare utilisation. Alternatively, this finding could also suggest women are more likely to have biologically indolent tumours, although we recently found no difference in tumour growth patterns by sex 40 . Second, there may be gender differences in receipt of HCC treatment.…”
Section: Discussionmentioning
confidence: 88%
“…However, we noted sex disparities in survival persisted after adjusting for BCLC stage, suggesting this difference is not entirely explained by healthcare utilisation. Alternatively, this finding could also suggest women are more likely to have biologically indolent tumours, although we recently found no difference in tumour growth patterns by sex 40 . Second, there may be gender differences in receipt of HCC treatment.…”
Section: Discussionmentioning
confidence: 88%
“…The slow median doubling time of HCC supports a rationale of a short delay in radiological surveillance given the challenges many centers are currently facing with COVID-19. (29)…”
Section: Stable Outpatients With Liver Disease And/or Hepatocellular mentioning
confidence: 99%
“…(22) Although semi-annual surveillance does increase early detection, (23) no studies have compared surveillance intervals of 4-8 months, and it is therefore reasonable to delay imaging if needed. A recent study by Rich et al (24) that looked at HCC doubling rates found that the median doubling time was 292 days; however, in 25.1% of patients, doubling time was <90 days along with a longer doubling time in patients with nonviral cirrhosis. Interestingly, rapid growth was seen mostly in smaller tumors whereas larger tumors exhibited more indolent growth.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 98%